NEOPTERIN IN PEDIATRIC LIVING-DONOR LIVER TRANSPLANT PATIENT - O. P. Shevchenko; G. A. Olefirenko; M. E. Pishchulina; I. E. Tsirulnikova; N. Sh. Muratova; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2011)
Neopterin (NP) is a marker of macrophages activation and is used for monitoring rejection in patients after heart, renal transplantation. The aim of the study was to evaluate plasma levels of NP in children before and after living-donor liver transplantation (LDLT) and its relationship with the postoperative course. The study included 72 children with end-stage liver disease (ESLD), aged 17 ± 11 (4–28) months before and after LDLT, 15 healthy children aged 9.9 ± 5.7 (3–21) months and 38 adult living-related liver donors, aged 37 ± 19 (18–56) years. In children with ESLD pre-transplant plasma levels of NP (25.2 ± 19.9 nmol/l) was significantly higher than in healthy donors or healthy children (5.5 ± 3.4 and 6.3 ± 2.7 nmol/l, resp., p < 0.01). After LDLT plasma level of NP was higher in children, who had graft dysfunction at days 28–32 (61.9 ± 30.9 nmol/l) after LDLT than in children who had no graft dysfunction (24.0 ± 5.6 nmol/l). The measurement of NP concentrations may be useful for monitoring of the postoperative course.